Exploring the relationship between organizational values and small team performance: a Delphi method application - García-Vidal, Gelmar; Sánchez-Rodríguez, Alexander; Pérez-Campdesuñer, Reyner; Martínez-Vivar, Rodobaldo (Serbian Journal of Management, 2020)
The objective of this article is to examine the relationships between organizational values and the performance indicators of an organization. Two work teams were analyzed in a restaurant. To achieve the objective, a Delphi method was developed that allowed knowing the level of consensus of the members of the teams studied among a group of previously identified values, allowing to identify those values that had greater importance and regulation for each team. Through the Mann-Whitney statistical test, the relationship between values and customer satisfaction and productivity were examined, aspects that were measured in the organization studied for each work shift, where the teams analyzed worked. The research made it possible to prove the relationship between values and customer satisfaction directly and productivity indirectly, demonstrating that the work team showed greater consensus on its values in terms of importance and level of regulation showed better results in the dependent variables analyzed. The research carried out allowed the quantitative validation of the hypothesis that the shared values that regulate the behavior of the employees studied are closely related to the performance indicators.